A novel electrochemical IL-6 sensor based on Au nanoparticles-modified platinum carbon electrode - Wang, Cai; Xin, Dongyuan; Yue, Qianwen; Wan, Huiyu; Li, Qian; Wang, Ying; Wu, Jingguo (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Interleukin-6 (IL-6) is a multifunctional polypeptide cytokine composed of two glycoprotein chains, which plays an important role in many cellular reactions, pathological processes, diagnosis and treatment of diseases and so on. The detection of IL-6 plays a promising role in the cognition of clinical diseases. Methods: 4-mercaptobenzoic acid (4-MBA) was immobilized on the gold nanoparticles modified platinum carbon (PC) electrode with the linker IL-6 antibody, and finally formed an electrochemical sensor that specifically recognized IL-6. Through the highly specific antigen-antibody reaction, the IL-6 concentration of the samples to be detected. The performance of the sensor was studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). Results: The experimental results showed that the linear detection range of the sensor for IL-6 was 100 pg/mL–700 pg/mL and the detection limit was 3 pg/mL. In addition, the sensor had the advantages of high specificity, high sensitivity, high stability and reproducibility under the interference environment of bovine serum albumin (BSA), glutathione (GSH), glycine (Gly) and neuron specific enolase (NSE), which provided a prospect for specific antigen detection sensor. Discussion: The prepared electrochemical sensor successfully detected the content of IL-6 in standard and biological samples, showing excellent detection performance. No significant difference was found between the detection results of the sensor and that of ELISA. The sensor showed a very broad prospect in the application and detection of clinical samples.